FDI INFLOW BETWEEN INDIA AND CHINA AND ITS IMPACT ON INDIAN ECONOMY - Meena, Ashok (International Journal of Psychosocial Rehabilitation, 2020)
India and China are the two main developed world emerging economic powers, both in Asia with wide domestic markets and cheap labour, which are also tempting FDI targets. With China joining the WTO, it has fallen for China, since it has first moved from the United States and has drawn more FDI than any other region, for the first time in FDI economic history. The key aim of the paper is to research comparatively the increasing structure and course of FDI in India and China. It is well recognized that FDI will supplement local growth initiatives in numerous ways, including the promotion of export productivity, the growth and enhancement of job skills, technical capacity building and financial development capital increase. India can learn a lot from China, our effective neighbor’s FDI policy and experience, to attract FDI and use it effectively for its growth. This chapter aims to examine and compare the progress of China’s FDI policy with India to allow us to learn from China’s experiences and to minimize our shortcomings and improve our FDI-related reforms.